Features of neurosteroid support of the state of alcohol dependence and its correction with dosed physical load in rats - Titkova, A. M.; Berchenko, O. G.; Veselovska, O. V.; Shliakhova, A. V. (Regulatory Mechanisms in Biosystems, 2020)
The role of steroid hormones in regulation of the functions of the emotiogenic limbic-neocortical system has been actively studied over the recent decades in order to determine their synthesis in the brain structures and role in the development and maintenance of dependence on psychoactive substances. However, the wide range of neurosteroids and their metabolites, as well as structural specific features of the synthesis of both neurohormones and their receptors make it difficult to obtain experimental data and interpret the results of the study. The participation of progesterone, cortisol, testosterone and estradiol in the development of alcohol dependence and the changes in their concentrations in the hypothalamus, hippocampus, amygdala and serum under the influence of dosed physical load were studied in 48 outbred adult male rats. Alcohol dependence was modeled by means of consuming food containing alcohol in the dose of 1.25 g of ethanol per 1 kg of rat body weight for two months. Dosed physical load was reproduced by a rat running in a wheel for 30 minutes daily for 7–10 days against the background of alcohol withdrawal. Neuroethological testing of craving for alcohol, EEG recording of the neocortex, hippocampus and amygdala was performed using a computer-diagnostic complex. The concentration of steroid hormones was determined in the structures of the brain and blood serum by the enzyme-linked immunosorbent assay. It was shown that dosed physical load attenuated the alcohol motivation of rats. On the 5th day it suppressed the electrographic manifestations of paroxysmal activity in the hippocampus and increased the level of the theta-rhythm in the amygdala, and on the 7th day it activated the neocortex with increasing beta-rhythm. This effect was accompanied by an increase in serum testosterone level against the background of maintaining functional tension of the peripheral glucocorticoid link of the hypothalamus-pituitary-adrenal system, which was observed in a state of alcohol dependence. The study demonstrated that progesterone plays the key role in allostatic rearrangements of the functional state of animals. An imbalance of progesterone levels was revealed in the brain structures: an increase – in the hypothalamus and hippocampus, and a decrease – in the amygdala under alcohol dependence; a decrease – in the hippocampus with recovery in the amygdala against the background of its high level in the hypothalamus, which occurs under the influence of dosed physical load on the rats under alcohol withdrawal. Thus, the dosed physical load is a promising approach to alcohol dependence rehabilitation.